Delicate matters - McConnell Duff, Alan (Mostovi (Ljubljana), 2006)
The article deals mainly with misunderstandings that may arise in translationswhich, although formally/grammatically correct, do not convey the desired meaning or effect. Working from the basis of authentic examples, the author provides guidelines as to how typical, recurrent errors may be avoided in specific language areas, including: word order and word choice, punctuation, sentence length, problematic structures (with an emphasis on negative forms), tone and register, meaning and ambiguity, metaphor - idiom and cliché, and the omnipresent source language influence.
Keywords: lektoriranje; napake; pomen; prevajanje